ERF108 from Poncirus trifoliata (L.) Raf. functions in cold tolerance by modulating raffinose synthesis through transcriptional regulation of PtrRafS. (2nd September 2021) - Khan, Madiha; Hu, Jianbing; Dahro, Bachar; Ming, Ruhong; Zhang, Yang; Wang, Yue; Alhag, Ahmed; Li, Chunlong; Liu, Ji‐Hong
SUMMARY: Ethylene‐responsive factors (ERFs) are plant‐specific transcription factors involved in cold stress response, and raffinose is known to accumulate in plants exposed to cold. However, it remains elusive whether ERFs function in cold tolerance by modulating raffinose synthesis. Here, we identified a cold‐responsive PtrERF108 from trifoliate orange ( Poncirus trifoliata (L.) Raf.), a cold‐tolerant plant closely related to citrus. PtrERF108 is localized in the nucleus and has transcriptional activation activity. Overexpression of PtrERF108 conferred enhanced cold tolerance of transgenic lemon, whereas virus‐induced gene silencing (VIGS)‐mediated knockdown of PtrERF108 in trifoliate orange greatly elevated cold sensitivity. Transcriptome profiling showed that PtrERF108 overexpression caused extensive reprogramming of genes associated with signaling transduction, physiological processes and metabolic pathways. Among them, a raffinose synthase (RafS)‐encoding gene, PtrRafS, was confirmed as a direct target of PtrERF108. RafS activity and raffinose content were significantly increased in PtrERF108 ‐overexpressing transgenic plants, but prominently decreased in the VIGS plants under cold conditions. Meanwhile, exogenous replenishment of raffinose could recover the cold tolerance of PtrERF108 ‐silenced plants, whereas VIGS‐mediated knockdown of PtrRafS resulted in cold‐sensitive phenotype. Taken together, the current results demonstrate that PtrERF108 plays a positive role in cold tolerance by modulation of raffinose synthesis via regulating PtrRafS. Our findings reveal a new transcriptional module composed of ERF108‐RafS underlying cold‐induced raffinose accumulation in plants. Significance Statement: A transcriptional module composed of ERF108‐ RafS in Poncirus trifoliata orchestrates upregulation of RafS gene expression and raffinose accumulation in response to cold stress.